Improving maneuverability of wheeled mobile robots by exploiting lateral slip - Sidek, Shahrul Na'im; Sarkar, Nilanjan (World Scientific and Engineering Acadddemy and Society (WSEAS), 2007)
We have witnessed a significant advancement in the field of mobile robot applications in the past two decades. From performing mission critical tasks such as in planetary exploration to simply doing household chores, this type of robots requires availability, reliability and safety of its operations. Consequently, there is a growing demand for fault tolerant control system (FTCS) for mobile robots where one of it major component is the fault detection and isolation (FDI) module. In our FDI study, one of the challenges in designing the robot model is to create an accurate and robust dynamics model. In this paper, the environment structure, which is the dynamic change in the surface characteristics, will be included. We will utilize Local Neural Model (LNM) in our robot modeling process. Wheel slippage is an event happened when the robot wheels lose their full grasp of the surface. This may cause the robot to deviate from its desired trajectory. On the other hand, the fault on the robot actuator may also lead to similar behavior but need different solution. In this paper we will expand the functionality of FDI module to infer a real actuator fault and wheel slippage in which, the solutions for both events can be combined in a single, common controller.